A fully digital approach to replicate functional and aesthetic parameters in implant-supported full-arch rehabilitation. Issue 3 (July 2018) - Monaco, Carlo; Ragazzini, Nicola; Scheda, Lorenzo; Evangelisti, Edoardo
Abstract: Purpose: The aim of this technical procedure was to use a fully digital technique (FDT) for full-arch implant support rehabilitation. The FDT was used to transfer the provisional restoration parameters to definitive restorations using intraoral scanners. Methods: Three sets of digital impressions were obtained. Through the first set, standard tessellation language 1 (STL1), provisional restorations screwed to implants and the surrounding gingival tissue was captured. STL2 consisted of intraoral scans of standardized scanbodies screwed to implants to collect 3D positioning data of implants. STL3 included the digital impression of provisional restoration out of the mouth in order to capture the gingival architecture and the peri-implant soft tissue that was not possible to transfer with the previous impressions. STL1, STL2, and STL3 were combined using computer-aided design (CAD) functions into a single file, STL4. Thus, STL4 contained information on the 3D implant positions, soft tissue architectures, occlusal relationships, correct occlusal vertical dimension and aesthetic features. Using STL4, the master models with implant analogues were 3D printed. Computer-aided design and computer-aided manufacturing milled (CAD/CAM-milled) aluminium bars and a resin prototype were produced to test the accuracy and the functional and aesthetic parameters. Titanium frameworks were digitally designed using STL4, milled using CAD/CAM, and finalized with pink resin and resin teeth. Conclusion: The FDT provided an effective fully digital protocol to capture all information for provisional full-arch implant restorations using an intraoral scanner and transfer that information to definitive restorations.